2016
DOI: 10.1371/journal.pone.0158594
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Disorder in Transmembrane Proteins: Roles in Signaling and Topology Prediction

Abstract: Intrinsically disordered regions (IDRs) are peculiar stretches of amino acids that lack stable conformations in solution. Intrinsic Disorder containing Proteins (IDP) are defined by the presence of at least one large IDR and have been linked to multiple cellular processes including cell signaling, DNA binding and cancer. Here we used computational analyses and publicly available databases to deepen insight into the prevalence and function of IDRs specifically in transmembrane proteins, which are somewhat negle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 51 publications
0
63
0
5
Order By: Relevance
“…The presence of IDRs is common in higher organisms. Indeed, a recent study found that IDRs are found in 50% of membrane proteins and usually are localized at the cytoplasmic face of the lipid bilayer (Bürgi et al, 2016). Computational studies also showed that multipass membrane proteins tend to have longer (;70 residues) IDRs facing the cytosol (Bürgi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of IDRs is common in higher organisms. Indeed, a recent study found that IDRs are found in 50% of membrane proteins and usually are localized at the cytoplasmic face of the lipid bilayer (Bürgi et al, 2016). Computational studies also showed that multipass membrane proteins tend to have longer (;70 residues) IDRs facing the cytosol (Bürgi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study found that IDRs are found in 50% of membrane proteins and usually are localized at the cytoplasmic face of the lipid bilayer (Bürgi et al, 2016). Computational studies also showed that multipass membrane proteins tend to have longer (;70 residues) IDRs facing the cytosol (Bürgi et al, 2016). This agrees with previous studies of plant DGAT1 indicating that the N-terminal region resides on the cytosolic face of the ER (Shockey et al, 2006;Weselake et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…16 However, it is now well established that intrinsically disordered proteins (IDPs) and regions (IDRs) are complete proteins (or segments of proteins) that lack a traditional globular secondary or tertiary structure, yet are fully functional. [17][18][19][20][21][22] Disordered regions generally are sequences of low complexity with a low proportion of hydrophobic residues and a high number of repeating residues with a preponderance of polar and charged residues. 23,24 This lack of bulky hydrophobic amino acids prevents the formation of an ordered core that comprises a traditional structured domain.…”
Section: Intrinsically Disordered Proteinsmentioning
confidence: 99%
“…In relation to the extra‐ and intracellular aqueous phases, volatile anesthetics achieve much higher concentrations in biomembranes (10–100 m m ), where they are accumulated preferentially at the membrane/water interface . Neurotransmitter release requires the fusion of synaptic vesicles to the presynaptic membrane, which is especially rich in disordered proteins . A pivotal step of this process is the self‐assembly of the so‐called ternary SNARE complex composed of three neuronal membrane proteins, including syntaxin, SNAP‐25, and synaptobrevin.…”
Section: Supporting Experimental Data and Observationsmentioning
confidence: 99%
“…ID sequences and domains are abundant not only in cytosolic proteins but also in membrane proteins and are involved in the regulation of crucial cellular signaling pathways . Computational data analysis has indicated that 40–50 % of human plasma membrane proteins possess ID regions of 30 or more consecutive residues localized preferentially on the cytoplasmic side …”
Section: Introductionmentioning
confidence: 99%